Biomass Production and Carbon/Nitrogen Ratio Influence Ecosystem Services from Cover Crop Mixtures. (1st January 2016) - Finney, Denise M.; White, Charles M.; Kaye, Jason P.
Abstract : Increasing plant diversity in agroecosystems with cover crops has been a successful strategy to augment ecosystem services from agriculture, and increasing diversity of cover crops may provide even greater benefits. Productivity and ecosystem services from multi‐species cover crop mixtures were measured in a 2‐yr field study of 18 cover crop treatments preceding conventionally tilled corn in central Pennsylvania. Increasing the number of species in a stand increased cover crop biomass ( R 2 = 0.15). However, mixing cover crop species that were complementary in phenology or N acquisition strategy did not result in mixtures that produced more biomass than high yielding monocultures. Increasing cover crop biomass was positively correlated with several ecosystem services, namely weed suppression, prevention of nitrate leaching, and aboveground biomass N, but negatively impacted inorganic N availability and corn yield in the subsequent cropping season. The cover crop C/N ratio was another determinant of ecosystem services positively related to nitrate leaching prevention, but negatively related to inorganic N availability and corn yield. This study supports the long‐held assumption that increasing biomass can enhance certain ecosystem services from cover crops; however, because the mixtures tested did not produce more biomass than high yielding monocultures, opportunities to increase biomass‐driven services with mixtures may be limited. The correlation between biomass C/N ratio and ecosystem services in this study also indicates that functional traits, as opposed to biomass alone, will be important for predicting ecosystem services from cover crop mixtures.